Fancy a stay at the Hotel California? Foreign direct investment, taxation and firing costs - Holger Görg (Leverhulme Centre for Research on Globalisation and Economic Policy, University of Nottingham, 2002)
This paper looks at the trade off between investment incentives and exit costs for the location of foreign direct investment (FDI). This issue does not appear to have been tackled in much detail in the literature. The analysis considers the effect of profit taxation (as a measure of investment incentives) and an index of hiring and firing costs (proxying exit costs) on the location of US outward FDI in 33 host countries. The results suggest that US FDI, in particular in manufacturing is negatively affected by the level of profit taxation and exit costs. Hence, if countries want to attract FDI it may not suffice that incentives are provided in order to ease the entry of multinationals. Instead, it also appears to be important that exit costs are at a level attractive to multinationals. In other words, multinationals may not check into an attractive looking Hotel California type host country if it is difficult to leave.
Keywords: F23; H25; J65; 330; foreign direct investment; exit costs; firing costs; investment incentives; taxation; Direktinvestition; Amerikanisch; Standortfaktor; Ertragsteuer; Kündigungsschutz; Schätzung; Welt